Pregnancy Outcome in Swiss-Webster Mice Infected With Chlamydia trachomatis. Issue 5 (1994) - Oshiro, Bryan T.; Graham, Jack M.; Blanco, Jorge D.; Seraj, Ibrahim M.; Bishop, Karen D.
Abstract : Objective: The objective of this study was to observe pregnancy outcomes in mice infected transvaginally with Chlamydia trachomatis . Methods: Pregnant mice were inoculated transvaginally with either C. trachomatis (CT) or sterile calf serum (CON) on pregnancy day 4. Pregnancy outcomes as well as genital tract histology and culture were compared. Statistical analysis was performed using Fisher's exact test and Student's t-test. Results: Twenty-four of 26 CT mice had positive uterine cultures for C. trachomatis. Inflammation occurred in 9 (34.6%) ( P = 0.002, 95% confidence interval = 1.7–3.5) and intrauterine fetal demise occurred in 5 (19.2%) ( P = 0.05, 95% confidence interval = 1.6–2.9) of CT mice. No mice in the CON group (0/24) had positive uterine cultures, developed inflammation, or experienced intrauterine fetal demise. Conclusions: Lower genital tract chlamydial infection is associated with intrauterine fetal demise in Swiss-Webster mice.